The tumour suppressing role of the circadian clock. Issue 7 (23rd January 2019) - Davis, Kate; Roden, Laura C.; Leaner, Virna D.; van der Watt, Pauline J.
Abstract: The circadian clock and the 24 h rhythms it generates are essential in maintaining regular tissue functioning. At the molecular level, the circadian clock comprises a core set of rhythmically expressed genes and gene products that are able to drive rhythmic expression of other genes to generate overt circadian rhythms. It has recently come to light that perturbations of circadian rhythms contribute to the development of pathological states such as cancer, and altered expression and/or regulation of circadian clock genes has been identified in multiple tumour types. This review summarises the important role the circadian system plays in regulating cellular processes, including the cell cycle, apoptosis, DNA repair, the epithelial‐to‐mesenchymal transition, metabolism and immunity and how its dysregulation has widespread implications and could be a critical player in the development of cancer. Understanding its role in cancer development is important for the field chronotherapy, where the timing of chemotherapy administration is optimised based on differences in circadian clock functioning in normal and cancer cells. This has been found to influence the patient response, minimising the side effects commonly associated with chemotherapy. © 2019 IUBMB Life, 2019